PHYSICO-CHEMICAL STUDY & EVALUATION OF SOIL HEALTH OF TODARAISINGHTEHSIL; TONK DIST. (RAJASTHAN) - Nama, Raghvendra Singh; Mishra, Manjul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
When assessing the quality of the soil, it is required to explain a comprehensive integration of static and dynamic chemical, physical and biological aspects. This is done in order to recognize diverse management and environmental scenarios. One of the key elements affecting crop yields is soil fertility and important soil components that affect soil fertility include macro- and micronutrients. A crucial component of sustainable agriculture production is soil characterization in relation to assessing the fertility status of soil of a region. Assessing the soil quality is crucial for determining the best management strategies to use for sustainable crop production. This study focused on some selected soil chemical parameters in a few blocks of Tonk district of Rajasthan state. It was observed that pH and Electrical Conductivity optimum, compared to the standard values provided by ICAR in various soil samples collected; While Organic Carbon, Phosphorus & Potassium were found to be below optimum values. Similarly Sulphur & Iron were found to be almost optimum and Zn, Mn & Cu were found to be above optimum values in most of the samples. Thus for better production of various crops, grown in this region like jowar, millet, wheat, groundnut and mustard, the soil can be improved with the recommendations of suitable fertilizers and organic manures.